2018
DOI: 10.2147/ijn.s157019
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy of intracranial glioma model mice with curcumin nanoliposomes

Abstract: BackgroundGlioma is the most aggressive and lethal brain tumor in humans, it comprises about 30 per cent of all brain tumors and central nervous system tumors.PurposeThe objective of this study was to create novel brain-targeting nanoliposomes to encapsulate curcumin as a promising option for glioma therapy.Patients and methodsHuman glioma cells (U251MG) were used to determine cell uptake efficiency and possible internalization mechanism of the curcumin-loaded nanoliposomes modified by a brain-targeting peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 35 publications
(33 reference statements)
1
26
0
Order By: Relevance
“…CM-NP exhibits a greater cytotoxic effect on GSCs compared with free curcumin. In keeping with our results, the anti-tumor effect of other types of curcumin nanoparticles, such as nanoliposome, was significantly greater than that of the free curcumin [26,27,50]. Niosome is among the promising drug carriers that act as a pool to release compounds in a steady, controlled, and sustained manner [51].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…CM-NP exhibits a greater cytotoxic effect on GSCs compared with free curcumin. In keeping with our results, the anti-tumor effect of other types of curcumin nanoparticles, such as nanoliposome, was significantly greater than that of the free curcumin [26,27,50]. Niosome is among the promising drug carriers that act as a pool to release compounds in a steady, controlled, and sustained manner [51].…”
Section: Discussionsupporting
confidence: 87%
“…Various biodegradable polymers of natural or synthetic origin have been used for curcumin nano-encapsulation [23][24][25]. The effects of different nano-sized particles of curcumin have been examined in GBM cells in both in vitro studies and clinical trials [26,27]. Curcumin nanoparticles have been shown to suppress the growth of multiple GBM cell lines through the reduction of stem-like tumor cells [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the hydrophobic nature, low water solubility, and physicochemical stability may limit its bioavailability [ 132 ], increasing evidence demonstrates that curcumin is able to cross the blood-brain barrier, thus yielding therapeutic benefits within the CNS [ 133 ]. However, extensive efforts are currently devoted to develop novel delivery systems (i.e., nanoparticles, liposomes, micellar systems, combination with piperine) [ 134 , 135 , 136 ] as well as curcumin derivatives [ 137 , 138 ], thus possibly overcoming these obstacles, while improving curcumin’s efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sustained release profile of our liposomal formulation at physiological temperatures and pH with a maximum of only 35% released curcumin cargo after 24 h is well aligned with the findings of Roy et al, who highlighted the connection between the lipid transition temperature of DPPC and the slower release kinetics of curcumin liposomes. 66 Using other lipids than DPPC, such as EPC or SPC for example, Chen et al reported releases of 45-50% of their total curcumin cargo already after 24 h. 46 Also, Zhao et al claim that their liposomal formulation of curcumin using soy lecithin released ≈50% after 24 h and already 80% of their cargo after 78 h. 70 Concluding these aspects, we could successfully establish a protocol for liposomal curcumin formulation, using 80.6% (w/w) DPPC and 15.6% (w/w) cholesterol and 10% trehalose as a cryoprotectant, and observed beneficial physicochemical properties, efficient drug loading and long-term stability of the liposomes.…”
Section: Discussionmentioning
confidence: 99%